A multidimensional rational design of nickel–iron sulfide and carbon nanotubes on diatomite via synergistic modulation strategy for supercapacitors - Li, Kailin; Hu, Zhufeng; Zhao, Renjun; Zhou, Jinfei; Jing, Chuan; Sun, Qing; Rao, Jinsong; Yao, Kexin; Dong, Biqin; Liu, Xiaoying; Li, Haiyan; Zhang, Yuxin; et al. (Journal of colloid and interface science, 2021)
[Display omitted] Based on their characteristics, transition metal layered double hydroxides have been of great scientific interest for their use in supercapacitors. Up until now, severe aggregation and low intrinsic conductivity have been the major hurdles for their application. In this work, nickel–iron sulfide nanosheets (NiFeSx) and carbon nanotubes (CNTs) were synthesized on diatomite using chemical vapor deposition and a two-step hydrothermal method to overcome these challenges. Synthesis of this composite successfully exploits the synergistic effect of multicomponent materials to improve the electrochemical performance. Diatomite is selected as a substrate to provide preferable surroundings for the uniform dispersion of nanomaterial on its surface, which enlarges the active sites that come in contact with the electrolytes, significantly improving the electrochemical properties. Combined with high conductivity and a synchronous sulfurization effect, the NiFeSx@CNTs@MnS@Diatomite electrode delivered a high specific capacitance of 552F g−1 at a current density of 1 A g−1, a good rate capability of 68.4% retention at 10 A g−1, and superior cycling stability of 89.8% capacitance retention after 5000 cycles at 5 A g−1. Furthermore, an asymmetric supercapacitor assembled via NiFeSx@CNTs@MnS@Diatomite and graphene delivered a maximum energy density of 28.9 Wh kg−1 and a maximum power density of 9375 W kg−1 at a potential of 1.5 V. This research lays the groundwork for ideal material preparation as well as a rational design for the electrode material, including property enhancement of diatomite-based material for use in supercapacitors.